Peace Journalism and News Coverage on Cyprus Conflict - Ersoy, Metin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2010)
ABSTRACT: Peace journalism is a new concept in the academic field and the media sector. It is important to stress that peace journalism is a new kind of reporting, and it involves news selecting and news framing for the journalism profession. This dissertation, which conducted on the Cyprus Conflict present for more than five decades, makes a contribution to the peace journalism conception of Johan Galtung. The findings of this dissertation, which analyses the coverage of the Cyprus Conflict on the press from the perspective of peace journalism, can also be applied to the other conflict zones of the world. In this study, the notion of peace journalism is explained by means of various examples taken from the Cypriot media. This study looks at the news stories reported by the Turkish Cypriot and Greek Cypriot newspapers on the matters relating to one another, from the perspective of peace journalism. The Cypriot media do allocate sizeable coverage for the stories related to the Cyprus Conflict. However it is observed that journalists do not necessarily stick to the principles of peace journalism as they prepare the reporting of the newsworthy stories on the conflict. The media in which peace journalism is not employed turns into a media instigating violence, hatred, and storm. Among the roles of journalists in battle areas include the crucial significance of approaching incidents from peace journalism perspectives. In light of the renewed negotiations in Cyprus for reunification, the Cypriot media should engage in responsible reporting. Keywords: Cyprus Conflict, News media, Peace journalism, News coverage, Framing. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Barış gazeteciliği akademik alan ve medya sektörü için yeni bir kavramdır. Barış gazeteciliğinin gazetecilik mesleği için yeni bir tür habercilik, haber seçimi ve haber çerçevesi olduğu önemle vurgulanmalıdır. Bu çalışma, 50 yıldan fazla devam eden Kıbrıs Sorunu’nu konu alıyor ve Johan Galtung’un barış gazeteciliği kavramına katkı sağlıyor. Çalışmanın bulguları ki barış gazeteciliği perspektifinden medyanın Kıbrıs Sorunu’nu yansıtmasını analiz ediyor, dünyadaki diğer çatışma bölgelerine de uygulanabilir. Çalışmada barış gazeteciliği anlayışı Kıbrıs medyasından alınan çeşitli örneklerle açıklanıyor. Bu çalışma Kıbrıs Türk ve Kıbrıs Rum gazetelerinin birbirleriyle ilgili konulardaki haberlerini barış gazeteciliği perspektifinden inceliyor. Kıbrıs’taki her iki medya da Kıbrıs Sorunu’yla ilgili haberlere önemli ölçüde yer veriyor. Buna rağmen, gazetecilerin haber değeri olan olayları haberleştirirken barış gazeteciliği prensiplerini yerine getirmedikleri gözlemleniyor. Barış gazeteciliğinin kullanılmadığı bir medya; şiddet, kin ve nefretin körüklendiği bir medya ortamı olarak karşımıza çıkıyor. Gazetecilerin çatışma bölgelerinde oynayabileceği roller arasında, olaylara barış gazeteciliği perspektifiyle yaklaşması önemlidir. Kıbrıs’ın birleştirilmesi için yeniden başlayan görüşmelerde, Kıbrıs medyası sorumlu habercililik yapmalıdır. Anahtar Kelimeler: Kıbrıs Sorunu, Haber medyası, Barış gazeteciliği, Haber kapsamı (coverage), Haber çerçevesi.
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication and Media Studies, Dept. of Communication and Media Studies, 2010. Supervisor: Prof. Dr. Suleyman Irvan.
Keywords: Communication and Media Studies; Peace Journalism - Cyprus; Greek Cypriot Media; turkish cypriot media; Cyprus conflict; Columnists; Cyprus Conflict News media Peace journalism News coverage Framing